Spatial patterns of subtidal nematodes and macrofauna assemblages along the estuarine gradient to assess benthic condition: Definition of homogenous sectors along a naturally stressed estuary (Portugal). - Adao, Helena (2010)
In transitional waters the definition of reference conditions must take into account the natural variability. Therefore, prior to the use of environmental quality assessment tools the estuarine stretches reflecting different physical-chemical and biological conditions should be defined in order to correctly establish the benthic specific reference conditions. The main goal of this study is the definition of homogeneous sectors along a naturally stressed estuary by: analysis of the structure and composition and diversity of nematodes and macrobenthos spatial distribution patterns along the estuarine gradients; and comparison of the environmental patterns change with the biodiversity trends. The subtidal assemblages (meio- and macrofauna) of the Mira estuary (considered a undisturbed system) were sample in the summer of 2006 and several environmental factors were determined. The environmental factors salinity and the particle size reflect an estuarine gradient. The Nematode and macrobenthos densities and assemblages composition change along the gradient, establishing homogenous sections: (i) the tidal and oligohaline sections are characterised by the presence of freshwater nematodes, the total densities and diversity reach the minimum values; macrobenthos is dominated by Gammarus, Chironomidae and Corbicula fluminae;(ii) in the mesohaline sections the nematode densities is lower and the diversity is poor, the dominant genera are Terschellingia and Sabatieira, Daptonema and Anoplostoma; macrobenthos is dominated by Corophium orientale, Leptocheirus pilosus and Ciathura carinata; (iii) in the polyhaline and euhaline sections the total densities and the diversity are higher, and the Nematode dominant genera are Paracomesoma and Synonchiella; the macrobenthic Heteromastus filiformes, C. orientale and Hediste diversicole are present in the polyhaline section While in the euhaline section the species Nephtys hombergii and Maldanidae are exclusive.